Characterization of Clinical and Paraclinical Features Associated With TS-HDS Autoantibody Seropositivity. (5th December 2022) - Rezk, Mohamed; Mirman, Igal; Berini, Sarah; Chompoopong, Pitcha; Klein, Christopher; Mills, John R.; Dubey, Divyanshu
Abstract : Objective: To evaluate neuropathy phenotypes and clinical outcomes associated with trisulfated heparin disaccharide (TS-HDS) autoantibodies. Background: TS-HDS autoantibody has been reported as a biomarker of immune-mediated neuropathy. However, studies evaluating the clinical associations of this autoantibody are limited. Design/Methods: Electronic medical records were reviewed to identify TS-HDS autoantibody seropositive patients and characterize their clinical and electrodiagnostic findings. Results: Seventy-seven TS-HDS-IgM seropositive (titer range 9000-350, 000) patients were identified (50 females; median age of onset was 48 years (range 9-83 years). Eleven patients were also positive for FGFR3-IgG (titer range 4000-19, 000). 70% (54/77) had clinical/paraclinical evidence of neuropathy (54/77, 70% of TS-HDS-IgM alone; 10/11, 91% of TS-HDS-IgM with coexisting FGFR3-IgG). The managing physician characterized an immune-mediated neuropathy in 30% (23/77) and 54% (6/11) of the TS-HDS-IgM only and TS-HDS-IgM with coexisting FGFR3-IgG seropositive patients, respectively. Small fiber neuropathy presented in 58% (45/77) and 63% (7/11) of TS-HDS-IgM only, and both antibodies seropositive patients, respectively. Length-dependent neuropathy was the most common neuropathy phenotype amongst TS-HDS IgM (43/54, 80%) and dual seropositive cases (7/11, 63%). Forty-one (53%) patients received immunotherapy, predominantly: IVIG (n = 37), IV solumedrol (n = 7), oral prednisone (n = 14), and mycophenolate mofetil (n = 12). Among these, 43% (15/35) with TS-HDS-IgM seropositivity alone had improvement in inflammatory neuropathy cause and treatment (INCAT) disability score or modified Rankin Scale (mRS), while 33% (2/6) of patients with dual seropositivity had INCAT and mRS improvement. TS-HDS-IgM titers had low discriminative ability to identify immunotherapy response with an AUC of 0.621. Conclusions: Neuropathy associations and clinical phenotypes amongst TS-HDS-IgM seropositive cases are variable. Furthermore, only a minority of cases are immunotherapy responsive, limiting the value of this biomarker in identifying immune-mediated neuropathies.